Επίδραση της προσαρμογής απομονώσεων του γένους Aspergillus σε μυκητοκτόνες ουσίες - Τσαγκάρη, Νικολέτα (Τμήμα Γεωπονικών Επιστημών, Βιοτεχνολογίας και Επιστήμης Τροφίμων, Σχολή Γεωτεχνικών Επιστημών και Διαχείρισης Περιβάλλοντος, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2012)
It is known that ascomycetous species of the genus Aspergillus are the causal agents of grape black rot and food spoilage in a number of products. Besides their phytopathological importance, black aspergilli (Aspergillus section Nigri) are also important as ochratoxin A (OTA) producing organisms which contaminate several agricultural products including grape derived products, coffee and cocoa. OTA is a mycotoxin that has been associated with carcinogenic, nephrotoxic, teratogenic and potentially neurotoxic properties. Despite the fact that fungicide usage for the management of Aspergillus infestations of vines is not a standard agricultural practice, their potential usage in extreme situations, in order to avoid high levels of OTA in the final product should not be excluded. Thus, in the presence study the adaptation effects of natural isolates of Aspergillus Section Nigri from Cyprus vineyards to fungicides, in terms of resistance level, aggression and OTA production were studied. Sixty isolates of the genus Aspergillus from three different vineyards in the municipality of Limassol were collected and their sensitivities to cyprodinil, fludioxonil, penconazole, thiabendazole (TBZ), belonging to groups with different mode of action and the formulated product Switch ®, a mixture of cyprodinil and fludioxonil were calculated using the Spiral Gradient Dilution method. Through successive exposures of an initial spore suspension mixture of the wild-type isolates in each of the aforementioned fungicides, strains with lower sensitivities were obtained and their resistance levels were calculated. It was found that the majority of the adapted strains showed multiple-resistance, except those that were originally selected to penconazole. The daily mycelial growth rates of adapted strains was also examined in vitro and showed that the mycelial growth of adapted strains was not statistically different regardless the presence of fungicides, except in the case of penconazole, where in its presence growth rates were lower than in untreated Petri dishes. Furthermore, the ability of the adapted strains to produce OTA was tested using high pressure liquid chromatography and it was found that 2 out of the 23 strains tested were mycotoxigenic. More specifically, one of the strains showed increased OTA production in the presence of TBZ, where the other strain produced decreased levels of the toxin. Finally, molecular identification was performed for selection of the adapted strains by sequencing of a portion of the calmodulin gene and it was found that 90% of isolates belonged to the A. tubigensis species, while 10% were identified as A. niger.
Keywords: Genes; Substances; Γονίδια; Ουσίες